Efektivitas Pembelajaran Matematika Melalui Pendekatan PMRI Berbantu Video Pembelajaran Terhadap Kemampuan Berpikir Kritis Siswa - Herlawan, Herlawan; Armin, Rismayani; Poa, Iin Rusandi (Edumatica : Jurnal Pendidikan Matematika, 2023)
This research aims to determine the effectiveness of mathematics learning through the Indonesian Realistic Mathematics Education (PMRI) approach assisted by learning videos on the critical thinking abilities of class VIII students at SMP Negeri 2 Baubau. This research is quantitative research using a quasi-experimental model. The student population consisted of class VIII students at SMP Negeri 2 Baubau, totaling 11 classes using a cluster random sampling technique so that the samples were class 8.2 and 8.3. The instruments used in this research were interviews and learning outcomes tests using N-gain analysis techniques and independent sample t test N-gain. Based on the research results, the results in the experimental class were in the effective category. This can be seen from the results of the N-gain score analysis showing the average N-gain score of 79.51 or 79.5%. Meanwhile, in the control class in the ineffective category, this can be seen from the results of the N-Gain score analysis showing that the average N-gain score is 25.16 or 25.2%. Meanwhile, from the results of the independent sample t test N-gain hypothesis test value, the Sig value was obtained. (2-tailed) is 0.000<0.05. Thus, it is concluded that there is a significant (real) difference in effectiveness between the use of the Indonesian realistic mathematics education (PMRI) approach assisted by learning videos and the use of conventional approaches to improve the critical thinking mathematical abilities of class VIII students at SMP Negeri 2 Baubau.